Pengaruh Leverage, Likuiditas, dan Intensitas Modal Terhadap Konservatisme Akuntansi Pada PT Gudang Garam Tbk - agustina, alin; Prathamy, Zahra; Moozanah, Siti; Juniarso, Andy (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2021)
In presenting financial statements, it is necessary to apply conservation accounting. Because to apply management flexibility in presenting financial statements. In writing this paper, the author raises a handful of discussions regarding the effect of leverage, liquidity and capital intensity on accounting conservation in an industry engaged in the tobacco sector. The method used in this research is a quantitative research method with secondary data obtained from the financial statements of the company PT Gudang Garam, Tbk in the 2018-2020 period. Techniques taken in collecting company data are documentation techniques and secondary data. In this study, the sample used was purposive sampling method, the aim was to obtain a representative sample based on predetermined criteria. The results obtained in this study indicate that liquidity does not have a significant effect on accounting conservatism. In a study that was conducted using only 3 periods, the authors hope that future research can carry out research in a wider period and with a larger company reach.